Studi tentang kepuasan pernikahan dalam penelitian psikologi di Indonesia - Rinto Wahyu Widodo (University of Merdeka Malang, 2021)
Every married couple yearns for satisfaction in their marriage. Although marriage satisfaction has a major effect on the integrity of the husband and wife relationship, it does not mean that marriage satisfaction is realized by married couples. In fact, many married couples decide to end their marriage relationship for several reasons. This article aims to look at the satisfaction of marriage in the last decade in Indonesia, and the implications for future research. The method used is literature study using data obtained from Google Scholar with the keyword